2004
DOI: 10.1080/14660820410020772
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the news: A survey of ALS patients and their caregivers

Abstract: Breaking the news of the diagnosis of amyotrophic lateral sclerosis (ALS) is a formidable task. To evaluate the process from the perspective of patients and caregivers, we surveyed 94 patient-caregiver pairs, as well as 50 unpaired patients and 19 unpaired caregivers. We asked respondents to evaluate the physician who first broke the news of the diagnosis based on the time spent discussing the diagnosis, and six attributes of effective communication of bad news derived from the SPIKES protocol (setting, percep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
65
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 29 publications
(26 reference statements)
3
65
1
Order By: Relevance
“…Diagnostic experiences can be particularly stressful for caregivers (70). However, studies suggested that communication at this time could be improved (38,42,55,71). McClusky et al, (71) found the average time spent imparting the diagnosis in a U.S. study was 30 minutes, and while 65% of doctors identified MND as a terminal disease, only 11% discussed palliative care options.…”
Section: Information and Communicationmentioning
confidence: 99%
“…Diagnostic experiences can be particularly stressful for caregivers (70). However, studies suggested that communication at this time could be improved (38,42,55,71). McClusky et al, (71) found the average time spent imparting the diagnosis in a U.S. study was 30 minutes, and while 65% of doctors identified MND as a terminal disease, only 11% discussed palliative care options.…”
Section: Information and Communicationmentioning
confidence: 99%
“…Two studies analyzed patient perceptions of this experience (Class III and Class IV). 2,3 Patients reported lack of empathy, insufficient explanation of the diagnosis and the course of the illness, and lack of information on where to get help.…”
Section: Analysis Of Evidencementioning
confidence: 99%
“…Raising a suspect of ALS and then breaking the news to the patient and relatives is a difficult task. Several papers have been devoted to this important step [3,24,25] and there is general awareness that this is a key step in the diagnostic and management process. Recently, several works have been dedicated to cognitive errors that physicians make in their diagnostic work-up [26,27].…”
Section: Independent Variablementioning
confidence: 99%